Identifying reflective modes in pre-service teachers’ written reflections on the implementation of project-based learning during the school practicum - Kaldi, Stavroula; Zafeiri, Stella (Frontiers in Education, 2023)
This study deals with written reflections from final-year undergraduate pre-service teachers on the implementation of project-based learning (PjBL) during the school practicum. The research focuses on highlighting undergraduate pre-service teachers’ meaning through reflexive thematic analysis as well as highlighting modes of expressing positions—according to a specific model categorizing these modes—on the implementation of child-centered instructional approaches such as Pj-BL. The research methodology included written reflections by 40 undergraduate student teachers in a 4-year university BA of preparing primary school teachers by applying the convenient sampling strategy. The participants were attending their final school teaching practice component of their studies. The study identifies prospective teachers’ positive points, concerns, and challenges when applying Pj-BL. The findings also indicate that prospective teachers need to further develop their reflective thinking skills to provide explanations and solutions and identify areas of personal improvement when they produce written reflective reports.